Energy balance in women during polar trekking—The POWER study - Pierre Bourdier; Jessica Devitt; Susan Gallon; Alexandre Zahariev; Isabelle Chery; Jacob R. Guzzetti; Stéphane Blanc; Chantal Simon; Audrey Bergouignan (Physiological Reports)
Abstract Polar expeditions pose a significant challenge, contributing to a substantial energy deficit. However, few data exist on nonprofessional individuals, and none of them have investigated the regulation of energy balance in female participants during an Arctic expedition. Eleven nonathlete female adults who reached the North Pole by ski in full autonomy were studied. Before and the day after the expedition, resting metabolic rate (RMR) was measured by indirect calorimetry, and fat mass (FM) and fat‐free mass (FFM) by bioelectric impedance. Total daily energy expenditure (TDEE) and activity‐related energy expenditure (AEE) were assessed with the doubly labeled water (DLW) during the expedition. Before and throughout the expedition, daily physical activity was evaluated using accelerometry and heart rate, while surface skin temperature was measured using an iButton placed on the chest. Additionally, fasting salivary cortisol concentration was measured throughout the expedition as a stress marker. The seven‐day trekking was associated with a TDEE of 18.67 [SD 1.72] MJ/d. Body mass decreased by 1.67 (SE 0.42) kg, mostly due to fat mass loss (−1.26 [0.39] kg), indicating a negative energy balance. These findings show that nonathlete females can greatly increase their AEE and, hence TDEE over a short time period. However, their food consumption was insufficient to meet their needs, thus leading to an energy deficit and body mass loss. Future studies should investigate whether this insufficient energy intake was due to a lack of available food or an inability to consume more, thereby deepening our understanding of energy balance regulation in extreme conditions.